Exogenous BR delayed peach fruit softening by inhibiting pectin degradation enzyme genes - Li, Jianzhao; Guo, Tingting; Guo, Meiling; Dai, Xiaonan; Xu, Xiaofei; Li, Yanju; Song, Zhizhong; Liang, Meixia (Frontiers in Plant Science, 2023)
Peach fruit deteriorates and senesces rapidly when stored at room temperature. Brassinosteroids (BRs) play an important role in regulating plant growth and development and maintaining fruit quality. However, little information is available on the effect of BRs on the senescence of harvested peach fruit. In this study, different concentrations of BR were used to treat 'Hongniang' peach fruit, and the results showed that 10 μM BR was the most beneficial concentration to delay the senescence of peach fruits. BR treatment delayed the decrease of fruit firmness, the release of ethylene, the increase in water-soluble pectin (WSP) and ionic-soluble pectin (ISP) content and the decrease in covalently bound pectin (CBP) content, inhibited the activities of pectin degradation enzymes, and inhibited the gene expression of PpPME1/3, PpPG, PpARF2, and PpGAL2/16. In addition, BR treatment also inhibited the expression of PpBES1-5/6. Cis-acting regulatory element analysis of pectin degradation enzyme promoters showed that many of them contained BES1 binding elements. All the above results showed that BR treatment had a positive effect on delaying the senescence of peach fruit and prolonging its storage period.